ANALYSIS OF HYBRID SOLAR AND WIND POWER GENERATION SYSTEMS - CHOO, CHEE YEAK (Universiti Malaysia Sarawak, (UNIMAS), 2022)
In recent past few decades, electricity generation in Malaysia mostly relies on non-renewable or carbon-based energy such as the combustion of fossil fuels and coals. Those sources create the emission of pollutants, especially carbon dioxide that leads to global warming and climate change. As a result, the Earth’s mean temperature has increased at an unusual level in these couple of years due to the emission of greenhouse gases. Therefore, renewable energy sources received important concern and attention in the early 2000s century, for instance, the use of solar energy, wind energy, and hydropower are replacing gradually the typical energy source to generate electricity for the consumer. The aim of this project is to analyse the performance of the hybrid system and to optimize the hybrid system up to the maximum output performance of the electricity. Due to inconsistent weather conditions and some uncertainties, renewable energy is harvesting and generating electricity in a hybrid manner. Furthermore, the unstable power distribution is solved by optimizing the output power using relevant mathematical algorithms. For this final year project, instead of using one renewable energy, it is encouraged to switch the power generation into a hybrid manner. A combination of solar and wind energy systems is modelled in this thesis writing. The necessary power converters are included, and different working scenarios are simulated using MATLAB Simulink for the purpose of performance analysis.